Vulnerability of Submarine Cable Network of Mainland China: Comparison of Vulnerability between before and after Construction of Trans-Arctic Cable System. (18th January 2021) - Xie, Yongshun; Wang, Chengjin
Abstract : The submarine optical-fiber cable (submarine cable) is a large connectivity infrastructure, which plays an important role in international communication, cyber-physical systems, and even national security. Although submarine cable network interruption may cause serious consequences, researching its vulnerability has not attracted much attention. This paper proposes a quantitative method to measure the vulnerability of the submarine cable network and evaluates the influence of the upcoming trans-Arctic cable (TAC) system on the submarine cable network of mainland China. To address this issue, first, the submarine cable network of mainland China is constructed. Further, methodology based on complex network and geospatial perspective is proposed to simulate the changes of network eigenvalues under different attacks and to quantitatively analyze the variation degree of network vulnerability. With the proposed method, the vulnerability of the submarine cable network of mainland China before and after construction of the trans-Arctic cable system is compared. The results reveal the key node countries and sea channels of the submarine cable network of mainland China and show the significance of the TAC system.